IκBζ augments IL-12– and IL-18–mediated IFN-γ production in human NK cells - Kannan, Yashaswini (American Society of Hematology, 2011)
Interferon-γ (IFN-γ) production by natural killer (NK) cells and cytotoxic lymphocytes is a key component of innate and adaptive immune responses. Because inhibitor of κB-ζ (IκBζ), a Toll-like receptor (TLR)/interleukin-1 receptor (IL-1R) inducible transcription factor, regulates IFN-γ production in KG-1 cells, we tested IκBζ's role in the classic lymphocyte pathway of IL-12/IL-18–induced IFN-γ. Upon stimulation with IL-12/IL-18, monocyte-depleted human peripheral blood lymphocytes expressed the 79-kDa form of IκBζ and released IFN-γ. CD56(+) NK cells were shown to be the IκBζ-producing lymphocyte subpopulation, which also released abundant IFN-γ in response to IL-12/IL-18. Importantly, IκBζ was undetectable in CD56(−) lymphocytes where IFN-γ release was 10-fold lower. In addition, small interfering RNA knockdown of IκBζ suppressed IFN-γ expression in CD56(+) cells. The association of IκBζ with the IFN-γ promoter was documented by chromatin immunoprecipitation. IFN-γ promoter activity from IκBζ overexpression was confirmed by luciferase reporter assay. Finally, IκBζ coprecipitated with p65 and p50 NF-κB in NK cells in response to IL-12/IL-18, suggesting that IκBζ's effects on IFN-γ promoter activity are coregulated by NF-κB. These results suggest that IκBζ functions as an important regulator of IFN-γ in human NK cells, further expanding the class of IκBζ-modulated genes.